Penerapan Sistem Informasi Pelayanan Konsumen Produk Kecantikan Berbasis Android Pada PT Jaya Fajar - Widyastuti, reni; Dhiana, Azis Sukma; Lestari, Wiji (Jurnal Informatika UPGRIS, 2022)
PT. Jaya Fajar Lestari has been a pioneer in beauty products since 1984. Since then the company has earned the trust, the loyalty of the public, and a reputation as an excellent provider of beauty products and services in the beauty business. One of the beauty services is beauty care and consultation, this service is in great demand and already has more than 100 consumers who are still handled manually so there are customer complaints about customer service such as being slow to inform the schedule of beauty treatments, the latest products, as well as answering customer complaints about the products that are available. used so that it requires an information system that can overcome these problems, namely an android-based system. The author proposes the application of this system with a waterfall system development model by describing the system with UML and java and android bases. This system is a solution to the problems of customer service PT. Jaya Fajar Lestari so that consumers can be served more intensively and comfortably in the use of this system and make it easier for the management of PT. Jaya Fajar Lestari in supervising the implementation of the company's business processes with the latest and most reliable reports